Whose Lifestyle Matters at Johannesburg Pride? The Lifestylisation of LGBTQ+ Identities and the Gentrification of Activism. (February 2022) - Conway, Daniel
In response to criticisms of whiteness and the privileging of middle-class South African experiences over the black majority and those in poverty, Johannesburg Pride expanded from a one-day event to include a 'Lifestyle Conference' in 2018. This article argues that rather than including broader South African LGBTQ+ experiences, rights and needs, the conference centred privileged and normative 'lifestyles' and emphasised individual agency, rather than making intersectional inequalities visible and a basis for collective action. Drawing from ethnographic research at Pride events, and interviews with Pride organisers and LGBTQ+ activists, this article builds on critiques and insights from social theory to analyse Johannesburg Pride's Lifestyle Conference; its aims, politics, marketing and messages. By exploring the raced and classed exclusions of Johannesburg Pride, this article addresses key gaps in the academic literature on Pride, and traces how the lifestylisation of LGBTQ+ identities obscures inequality and contributes to the neoliberal co-option of Pride.